EAR-EEG signal transmission in WSN to evaluate co-channel interference of OLSR routing through residual of Fractional spline wavelet for auditory hallucination diagnosis - Nithya et al., V. (International Journal of Advanced Science and Technology, 2019)
Schizophrenia a mental illness causes due to chemical imbalance in brain. The imbalance causes interference in person emotions and thinking. In delusion cases, the patients believe in false things, which occur due to persecution, delusion of grandeur. The false belief of patient result in thinking about different things and the patients thought jumps from one thought to other resulting in thinking without any logic. The irrational behaviour of schizophrenic patients, make the listeners hard to follow. The schizophrenic patients believe that they have controlled by others and have extraordinary abilities and powers. Furthermore, the patients hear about things when no one is around (auditory hallucination). Diagnosing, auditory hallucination and delusions is a challenging task since, the person experiencing schizophrenia talk about different things at a time. In this paper, EAR-EEG signal from ear has acquired, transmit in wireless sensor network through OLSR routing and process with fractional spline wavelet transform to study the co-channel interference due to nodes during transmission for hallucination and delusion diagnosis.